COMBINED FUEL SUPPLY SAFETY SYSTEM FOR INTERNAL COMBUSTION ENGINE - Simonyan Arman Robert; Mosikyan Hakob Karapet; Balayan Razmik Makar; Shaghoyan Viktorya Ashot (Reviews of Modern Science, 2024)
The article considers the necessary conditions for ensuring the fire and explosion safety system of gas cylinder/compressed gas vehicles, as well as the circumstances and causes of gas leaks. A system of equipment for recording cases of gas leaks from automobile gas devices and facilities during operation is designed and recommended. It can inform the driver about the fact of gas leakage and stop the supply of gas by closing the valve of the cylinder. The developed system is a complex of technical means, the work of which is autonomous and begins to operate from the moment of the appearance of electric current in the electric circuit of the car. Implementation of the system will make it possible to prevent accidents in case of a containment violation of the gas equipment in the automobile.